1998
DOI: 10.1029/98gl01987
|View full text |Cite
|
Sign up to set email alerts
|

The 1996 Peru tsunamigenic earthquake: Broadband source process

Abstract: Abstract. We investigate the spatio-temporal complexity of than a few tens of cm at various sites in the Pacific, the Marmoment release of the February 21, 1996 Peru earthquake quesas experienced locally water waves on the order of 2 m (M w 7.5). We use a non-linear source tomographic technique, [Heinrich et al., 1998]. We investigate the source process of based on simulated annealing, to invert surface wave source the 1996 Peru earthquake using two different methods: a) spectra for the slip distribution on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 12 publications
1
48
1
4
Order By: Relevance
“…There is a pattern of earthquake directivity along the coast of western South America (Figure 1). In the north, earthquakes rupture to the north (1979 M w 8.2 Colombia event [ Kanamori and Given , 1981; Beck and Ruff , 1984]), in the middle, earthquakes are bilateral (1996 M w 7.5 Peru earthquake [e.g., Ihmlé et al , 1998], the 1960 M w 7.6 Peru earthquake [ Pelayo and Wiens , 1990], and the 1966 M w 8.0 Peru event [ Beck and Ruff , 1989]), and south of about 12°S, directivity is southerly (the 1960 M w 9.5 Chile event [e.g., Benioff et al , 1961]; the 1974 M w 8.1 Peru event (bilateral, but most moment to south [ Langer and Spence , 1995]); and the 1985 M w 8.0 Chile event (ruptured updip and to the south [ Choy and Dewey , 1988; Mendoza et al , 1994]), as well as the 1995, 1996, and 2001 earthquakes). On the basis of these patterns, we hypothesize that the future rerupture of the 1877 earthquake will rupture to the south.…”
Section: Discussionmentioning
confidence: 99%
“…There is a pattern of earthquake directivity along the coast of western South America (Figure 1). In the north, earthquakes rupture to the north (1979 M w 8.2 Colombia event [ Kanamori and Given , 1981; Beck and Ruff , 1984]), in the middle, earthquakes are bilateral (1996 M w 7.5 Peru earthquake [e.g., Ihmlé et al , 1998], the 1960 M w 7.6 Peru earthquake [ Pelayo and Wiens , 1990], and the 1966 M w 8.0 Peru event [ Beck and Ruff , 1989]), and south of about 12°S, directivity is southerly (the 1960 M w 9.5 Chile event [e.g., Benioff et al , 1961]; the 1974 M w 8.1 Peru event (bilateral, but most moment to south [ Langer and Spence , 1995]); and the 1985 M w 8.0 Chile event (ruptured updip and to the south [ Choy and Dewey , 1988; Mendoza et al , 1994]), as well as the 1995, 1996, and 2001 earthquakes). On the basis of these patterns, we hypothesize that the future rerupture of the 1877 earthquake will rupture to the south.…”
Section: Discussionmentioning
confidence: 99%
“…We also estimate radiated seismic energy for tsunami earthquakes for which source time functions have been published. Six historic tsunami earthquakes believed to be associated with faulting rather than submarine slumps have been well studied with information on moment release history: 1946 Alaska [ Johnson and Satake , 1997], 1960 Peru [ Pelayo and Wiens , 1990], 1963 and 1975 Kurile [ Pelayo and Wiens , 1992], 1992 Nicaragua [ Ihmlé , 1996], 1996 Peru [ Ihmlé et al , 1998]. Our estimates of the radiated energy for the tsunami earthquakes use the duration and maximum moment rate from these published time functions (Figure 6).…”
Section: Energy Estimatesmentioning
confidence: 99%
“…The rigidity for such a shallow fault may be small; if it is 1 × 10 10 N/m 2 , then the seismic moment becomes 3 × 10 20 Nm (M w 7.6), a value similar to the Harvard CMT solution. HEINRICH et al (1998) also modeled this tsunami on the basis of the seismic model of IHMLÉ et al (1998). Their source is also a shallow and narrow fault near the trench, although they concluded that the rigidity is 2 × 10 10 N/m 2 .…”
Section: The 1996 Peru Tsunami Earthquakementioning
confidence: 99%